AKT expression is associated with degree of pathologic response in adenocarcinoma of the esophagus treated with neoadjuvant therapy - Saeed, Nadia; Shridhar, Ravi; Hoffe, Sarah; Almhanna, Khaldoun; Meredith, Kenneth L. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Introduction: Neoadjuvant chemoradiation (NCRT) has become standard in the treatment of locally advanced esophageal adenocarcinoma (EAC) with survival correlated to degree of pathologic response. The PI3K/AKT/mTOR pathway plays an important role in tumorgenesis and resistance. We sought to elucidate the role of this pathway in patients with EAC who received NCRT. Methods: After IRB approval, a prospective trial was initiated in which patients with EAC underwent endoscopic biopsies of normal and tumor tissue prior to instituting NCRT. Patients then proceeded to esophagectomy. The pre-treatment tissues underwent gene expression profiling. SAM method was used to analyze expression of AKT within normal and tumor tissue. Expression was then correlated to degree of pathologic response. Results: One-hundred patients were consented for the study, of which 67 met final eligibility. Nineteen patient’s tumors ultimately underwent gene expression profiling via microarray. The differential expression of all AKT isoforms in tumor tissue was markedly overexpressed compared to normal tissue (P=6×10−5). There were 3 patients designated as pNR, 6 as pPR, and 10 as pCR. Partial and non-responders had higher expressions of AKT compared to pCR with the non-responders consistently illustrated the highest expression of AKT (P=0.02). There was a significant correlation between individual isoforms of AKT-1, AKT-2, and AKT-3 and degree of pathologic response (P=0.002, 0.04, and 0.04 respectively). Conclusions: AKT is overexpressed in patients with AC of the esophagus. Moreover, pathologic response to NCRT may be correlated with degree of AKT expression. Additional data is needed to clarify this relationship to potentially add targeted therapies to the neoadjuvant regimen.